Preparation method of iron-phosphorus acid with adjustable titanium-doped iron-phosphorus acid

CN122916082APending Publication Date: 2026-10-16GUIZHOU PHOSPHATE KAIRUI TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611286998.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种掺钛量可调的铁法钛掺杂磷酸铁制备方法,该工艺能够解决现有掺钛磷酸铁制备工艺中引入杂质离子导致产品纯度降低、废水处理成本高以及钛掺杂不均匀等技术问题

Benefits of technology

1.填补铁法原位掺钛技术空白,环保优势与纯废优势突出

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916082A_ABST
    Figure CN122916082A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of titanium-doped iron phosphate, and particularly discloses a preparation method of iron-process titanium-doped iron phosphate with adjustable titanium-doping amount, which comprises the following steps: dissolving iron, preparing a bottom liquid, two-stage oxidation, aging, washing, drying and calcination, wherein the clear iron dissolving liquid is prepared by dissolving high-purity iron blocks or iron powder in phosphoric acid, the titanium oxysulfate is diluted according to the mass and then mixed with the iron dissolving liquid to prepare the bottom liquid, the ferrous iron is stably oxidized and titanium is synchronously doped in the crystal lattice by the two-stage temperature control and the segmented dropwise addition of hydrogen peroxide, the material slurry is aged at constant temperature after turning white, and finally the finished product is obtained through washing, drying and calcination. The application does not need an additional alkaline regulator in the whole process, can stably control the titanium content of the finished product in a wide range of 4000-16000 ppm, solves the problems of uneven titanium doping, easy generation of impurity phases in high-doping and poor batch stability in the traditional process, and has high product purity and good crystallinity, and is suitable for the preparation of power and energy storage type lithium iron phosphate positive electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of titanium-doped iron phosphate technology, specifically to a method for preparing titanium-doped iron phosphate using an iron-based method with adjustable titanium doping levels. Background Technology

[0002] Iron phosphate is a key precursor for the preparation of lithium iron phosphate (LFP) cathode materials for lithium-ion batteries. Its purity, morphology, and doping uniformity directly affect the electrochemical performance and processing properties of the final LFP product. Studies have shown that introducing titanium doping during the precursor synthesis stage can effectively improve the tap density, electronic conductivity, and rate performance of LFP materials. Therefore, the preparation of titanium-doped iron phosphate has become an important technical approach to improve the overall performance of LFP cathode materials.

[0003] Currently, the preparation method of titanium-doped ferric phosphate typically uses a mixture of iron and titanium sources as the base solution, then adds a phosphorus source to the base solution for a co-precipitation reaction, and finally obtains titanium-doped anhydrous ferric phosphate through pressure filtration, washing, and calcination. This co-precipitation reaction is generally based on the ammonium method, iron method, or sodium method for preparing ferric phosphate. Among these, the ammonium method is the most widely used process due to its lower raw material cost. The ammonium method uses ferrous sulfate as the iron source and monoammonium phosphate as the phosphorus source. During the oxidation precipitation process, ammonia water is used as a pH adjuster and precipitant, while a titanium source such as titanium sulfate or titanium oxysulfate is introduced to achieve co-precipitation doping of titanium elements in ferric phosphate. The iron source is usually derived from titanium dioxide byproducts. The sodium method, on the other hand, uses sodium hydroxide as a pH adjuster and precipitant. For example, patent CN111908441B discloses a wet method for preparing titanium-doped ferric phosphate. This method involves dissolving ferrous salt in water, adding phosphoric acid and iron filings to react, filtering to obtain a clear solution, adding a saturated titanium salt solution and stirring until homogeneous, oxidizing with an oxidizing agent, and then adding an alkaline solution to adjust the pH to 1.2-1.8. The mixture is then heated and aged, and finally washed, dried, and sintered to obtain the finished titanium-doped ferric phosphate. In this method, the alkaline solution is ammonia or sodium hydroxide, essentially an ammonium or sodium method for preparing ferric phosphate. However, this preparation method has the following significant drawbacks: First, the addition of an alkaline adjuster introduces impurities, affecting product purity. After oxidation, sodium hydroxide or ammonia still needs to be added to adjust the pH, inevitably introducing sodium into the system. + or NH4 +Added ions, such as ferric phosphate ions, are easily trapped inside the ferric phosphate precipitate particles during co-precipitation, and are difficult to completely remove even after multiple washes. Studies have shown that the purity of ferric phosphate products prepared by the ammonium process is "slightly inferior." Residual ammonium ions may also decompose and generate gas during subsequent high-temperature calcination, affecting the density and electrochemical performance of the material. Furthermore, the ammonium process uses ferrous sulfate as a raw material, which also introduces sulfate ions; incomplete removal of impurity ions will lead to a decrease in product purity. Secondly, the treatment cost of ammonia / sodium-containing wastewater is high, and environmental pressure is significant. The ammonium process generates a large amount of mother liquor and wash water during production, which contains a large amount of NH4. + and SO4 2- This type of high-salt, ammonia-nitrogen-containing wastewater cannot be directly discharged and requires a dedicated wastewater treatment system. Wastewater treatment typically involves first adjusting the pH to alkaline, followed by MVR evaporation and concentration to obtain ammonium sulfate. This process is energy-intensive and expensive to operate. The sodium process faces similar problems in treating sodium-containing wastewater. Third, the uniformity of titanium doping is difficult to control effectively. In ammonium co-precipitation, the hydrolysis rate of titanium differs from the precipitation rate of iron phosphate, easily leading to uneven distribution of titanium within the particles. The existing technology CN111908441B uses a "coating co-precipitation" route, which essentially achieves stepwise precipitation by controlling pH to preferentially precipitate the titanium source followed by iron phosphate coating. This stepwise precipitation method requires high process control; if the hydrolysis rate of titanium and the precipitation kinetics of iron phosphate are not well matched, titanium may accumulate inside the particles rather than be uniformly distributed, affecting the performance consistency of the final lithium iron phosphate material.

[0004] To address the aforementioned issues, there is an urgent need to develop a method that can completely avoid the addition of external alkaline regulators and eliminate NH4 at its source. + Or Na + A method for preparing titanium-doped iron phosphate that can achieve uniform lattice doping of titanium by introducing impurities and generating ammonia / sodium-containing wastewater. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a method for preparing titanium-doped iron phosphate using an iron-based method with adjustable titanium doping levels. This process can solve the technical problems in existing titanium-doped iron phosphate preparation processes, such as the introduction of impurity ions leading to reduced product purity, high wastewater treatment costs, and uneven titanium doping.

[0006] To address the above technical problems, in a first aspect, the present invention provides a method for preparing titanium-doped iron phosphate using an iron-based method with adjustable titanium doping levels, comprising the following steps: S1. Iron dissolving reaction: Iron source is mixed with phosphoric acid to carry out an iron dissolving reaction, and the iron solution is obtained after filtration to remove impurities; wherein, the iron source is iron block or iron powder; S2. Dilution: Dilute the molten iron solution with water to adjust the total iron concentration and pH of the system, and obtain a diluted solution; S3. Preparation of the base solution: Calculate the required amount of titanium source to be added according to the target titanium doping amount, and then add the titanium source to the diluent and mix evenly to obtain the reaction base solution; S4. Preparation of hydrogen peroxide: Divide the hydrogen peroxide into two parts. The first part is 20% to 80% of the total amount of hydrogen peroxide used, and the second part is the remainder. S5. First stage low-temperature oxidation: The first part of hydrogen peroxide is added to the reaction substrate at a dropping rate of 2.8~28 mL / min to carry out the first oxidation reaction and obtain the first oxidation solution; wherein, the temperature of the first oxidation reaction is 55~85℃; S6. Second stage high-temperature oxidation: The second part of hydrogen peroxide is added to the first oxidation solution at a dropping rate of 2.8~28 mL / min to carry out a second oxidation reaction to obtain a second oxidation solution; wherein, the temperature of the second oxidation reaction is 80~100℃; S7. Aging: After the second oxidation solution turns pinkish-white, it is kept at a constant temperature for aging to obtain an aged solution; S8. Post-processing: The aging liquid is subjected to solid-liquid separation to obtain a filter cake. The filter cake is washed with pure water, dried, crushed, and calcined to obtain anhydrous titanium-doped iron phosphate product.

[0007] Furthermore, in S1, the mass concentration of phosphoric acid is 15%~60%; the iron dissolution reaction is carried out under constant temperature water bath conditions, the water bath temperature is 25~90℃, stirring is required during iron dissolution, and the stirring speed is 150~500rpm; the phosphorus-iron molar ratio of phosphoric acid to iron source is 2.0~3.0; and the purity of the iron block is ≥99.9%.

[0008] Furthermore, in S2, the total iron mass concentration of the system is 2.5%~4.5%, and the pH is 1.8~2.2.

[0009] Furthermore, in S3, the titanium source is obtained by diluting a titanium oxysulfate solution with water; wherein the total mass of the diluted solution is 4 to 12 times the mass of the titanium oxysulfate solution before dilution.

[0010] Furthermore, in S4, the total molar amount of hydrogen peroxide is 1.1 to 1.8 times the total molar amount of iron in the reaction substrate.

[0011] Furthermore, in S5 and S6, both the first oxidation reaction and the second oxidation reaction require stirring, with a stirring speed of 200~600 rpm.

[0012] Furthermore, in S7, the heat preservation and aging time is 1 to 4 hours.

[0013] Furthermore, in step S8, the washing with pure water is performed at least twice, and the amount of pure water used in each wash is 4 to 6 times the mass of the filter cake to be washed. The washing temperature is 55 to 65°C. The aged mother liquor obtained after solid-liquid separation can be reused in step S1 to participate in the iron dissolving reaction. The drying temperature is 80 to 150°C, and the drying time is 3 to 12 hours. The calcination temperature is 600 to 700°C, and the calcination time is 2 to 6 hours.

[0014] Secondly, the present invention provides a titanium-doped iron phosphate, prepared by the method of the first aspect, wherein the titanium doping content in the titanium-doped iron phosphate is 4000~16000ppm, the D50 is 6.51~6.76μm, and the specific surface area is 5-6m². 2 / g, titanium is uniformly distributed within the crystal lattice, with no free impurities.

[0015] Compared with existing technologies, this solution has the following advantages: 1. Fills the gap in in-situ titanium doping technology using the iron-based method, with significant environmental and waste-to-material advantages. Existing preparation methods for titanium-doped ferric phosphate all rely on ammonium or sodium processes, which depend on alkaline adjusters such as ammonia or sodium hydroxide to control the precipitation pH. This necessitates the addition of external cations NH4+. + Or Na + The introduction of NH4+ and the generation of large amounts of high-salt, ammonia / sodium-containing wastewater. This invention is the first to achieve stable in-situ titanium doping in a pure iron system. Elemental iron powder or iron blocks are reacted with phosphoric acid to generate ferrous dihydrogen phosphate solution. Titanium sources are directly introduced into this system for doping without the need for any alkaline neutralizing agents, thus eliminating NH4+ at its source. + Na + The introduction of exogenous cations is another key aspect. This technical approach not only completely eliminates the generation of ammonia nitrogen wastewater, but also produces a single-component dilute phosphoric acid system from the aging mother liquor, which can be directly reused in the iron smelting section, achieving internal process circulation and significantly reducing environmental governance costs and investment in wastewater treatment equipment. Furthermore, because the system contains no residual exogenous cations, the resulting titanium-doped iron phosphate product has extremely low impurity content and high purity, fully meeting the stringent purity requirements of high-end power battery cathode materials for precursors.

[0016] 2. The synergistic effect of "pre-dispersion of titanium doping + two-stage rate-controlled oxidation" results in uniform doping and no impurity phase formation. Titanium sources such as titanium oxysulfate have extremely rapid hydrolysis rates, readily hydrolyzing in conventional coprecipitation systems to form metatitanic acid or titanium dioxide impurities, leading to uneven doping or even doping failure. This is a core technological bottleneck restricting the industrialization of titanium-doped iron phosphate. This invention innovatively employs a pre-doping process using a pre-mixed titanium source before oxidation: after the iron dissolution reaction is completed, the ferrous system is first adjusted to a stable concentration and pH range, at which point the Fe in the system... 2+ With PO43- They coexist stably in a soluble complex form; subsequently, a diluted titanium oxysulfate solution was added to the substrate. Since no oxidant had been introduced into the system, Fe... 2+ Without oxidation and precipitation, titanium ions can fully diffuse in the reaction solution, achieving uniform pre-dispersion at the molecular level. This fundamentally avoids preferential hydrolysis of the titanium source due to excessively high local concentrations. Furthermore, this invention incorporates a two-stage rate-controlled oxidation process, which, through the segmented addition of the oxidant and corresponding temperature range control, smoothly regulates the Fe content. 2+ The oxidation rate and nucleation and growth rate of iron phosphate, making Ti 4+ Hydrolysis-condensation kinetics and Fe 3+ The precipitation kinetics of Ti are highly matched. 4+ with Fe 3+ Simultaneous precipitation and synergistic embedding into the lattice are achieved. Pre-dispersion of titanium provides a thermodynamic basis for uniformity, while two-stage rate-controlled oxidation provides kinetic assurance for simultaneous doping. The synergistic effect of the two ensures that even under high doping conditions, titanium can be uniformly distributed in the iron phosphate lattice, effectively avoiding the formation of free titanium phosphate or titanium dioxide impurity phases, and fully leveraging the modification effect of titanium doping on the tap density and electronic conductivity of lithium iron phosphate materials.

[0017] 3. The titanium doping amount is adjustable within a wide range with good batch consistency and controllable mass production. In this invention, there is a good linear correlation between the finished titanium content and the amount of titanium oxysulfate added, which allows for precise control of the titanium doping amount over a wide range. By simply adjusting the amount of titanium source added, the finished titanium content can be freely set within the range of 4000–16000 ppm, flexibly meeting the differentiated requirements of various application scenarios for titanium doping. More importantly, the pre-dispersion process ensures the uniform distribution of the titanium source in the reaction solution, and the two-stage rate-controlled oxidation process ensures a high degree of controllability in the precipitation process. This allows the fluctuation of titanium content within a single batch to be stably controlled within ≤±200 ppm, and the titanium element distribution, crystal morphology, particle size, and particle size distribution of products from different batches all exhibit excellent consistency. This highly controllable doping system significantly reduces the difficulty of quality control during mass production, and has good prospects for industrial application and economic benefits. Attached Figure Description

[0018] Figure 1 This is a SEM image of the titanium-doped iron phosphate prepared in Example 1 of the present invention; Figure 2 EDS image of titanium-doped iron phosphate obtained in Example 1 of this invention; Figure 3 This is a SEM image of the titanium-doped iron phosphate obtained in Example 2 of the present invention; Figure 4EDS image of titanium-doped iron phosphate obtained in Example 2 of this invention; Figure 5 This is a SEM image of the titanium-doped iron phosphate obtained in Example 3 of the present invention; Figure 6 EDS image of titanium-doped iron phosphate obtained in Example 3 of this invention; Figure 7 This is a SEM image of the titanium-doped iron phosphate obtained in Example 4 of the present invention; Figure 8 This is the EDS image of the titanium-doped iron phosphate obtained in Example 4 of the present invention. Detailed Implementation

[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] Example 1 (1) Iron dissolution: Mix 85% industrial phosphoric acid with pure water to prepare a phosphoric acid solution with a mass fraction of 30%. Add high-purity iron powder at a phosphorus-iron molar ratio of 2.5. Place the solution in a constant temperature water bath at 70℃ and stir at 300 rpm until the iron powder is completely dissolved. Filter to remove undissolved residues and obtain a clear iron dissolution solution.

[0021] (2) Preparation of the base solution: Add pure water to the clear molten iron solution to dilute it, adjust the total iron mass concentration to 3.5%, and adjust the pH value of the system to 2.0; calculate the amount of titanium sulfate solution required to produce 4000ppm titanium phosphate based on the mass of anhydrous iron phosphate that can be obtained from the molten iron solution, dilute it with water by 6 times by mass, add all the diluted titanium solution to the above molten iron solution, stir and mix well to obtain the reaction base solution.

[0022] In this step, the mass (g) of titanium oxysulfate used is equal to the theoretical mass (g) of anhydrous iron phosphate. Target Ti doping amount (ppm) / Ti mass fraction in titanium oxysulfate (ppm). The calculation method is as follows: (a) Mass of anhydrous ferric phosphate (mFePO4 = nFe × 150.82 g / mol) (b) Mass of titanium oxysulfate used (g) = theoretical mass of anhydrous ferric phosphate (g) The target amount of Ti doping (ppm) / Ti mass fraction in titanium oxysulfate (ppm) is given, where the mass fraction of titanium (as TiO2) in the titanium oxysulfate solution is determined directly by ICP detection of the Ti element content.

[0023] The amount of titanium source added is determined by converting the target titanium content. Specifically: the theoretical mass of anhydrous iron phosphate is calculated based on the total molar amount of iron (nFe) in the molten iron solution. This mass is then multiplied by the target titanium doping amount (ppm level) to obtain the required mass of titanium element (mTi). The actual mass of titanium source solution added is then calculated based on the mass fraction of titanium element (calculated as TiO2) in the titanium oxysulfate solution used. The target titanium doping amount can be selected within the range of 4000~16000 ppm.

[0024] (3) First stage of low temperature oxidation: The reaction base liquid is heated to 75°C, the stirring speed is fixed at 400 rpm, and the first part of hydrogen peroxide is added dropwise at a rate of 14 mL / min. The amount of the first part of hydrogen peroxide is 40% of the total hydrogen peroxide; the total molar amount of hydrogen peroxide is 1.4 times the total iron in the system.

[0025] (4) Second stage of high temperature oxidation and aging: After the first stage of addition is completed, the system is heated to 90°C. The remaining hydrogen peroxide is added at a rate of 14 mL / min while maintaining the same stirring speed. After the addition is completed, stirring is continued. Timing is started when the slurry turns completely pinkish-white. The slurry is kept at 90°C for 2 hours for aging.

[0026] (5) Filtration and washing: The aged slurry is filtered and the filter cake and aged mother liquor are collected separately. The filter cake is washed twice with pure water at 60℃, and the amount of water added each time is 4 times the mass of the filter cake. The aged mother liquor can be recycled to S1 for reuse.

[0027] (6) Drying and calcining: After washing, the filter cake is dried at 80℃ for 12 hours, crushed, and calcined at 650℃ for 3 hours in air atmosphere. After cooling and crushing, titanium-doped iron phosphate product is obtained.

[0028] The finished product was found to contain 4168 ppm of titanium, and its various performance indicators are shown in Table 1.

[0029] Example 2 (1) Iron dissolution: Mix 85% industrial phosphoric acid, aged mother liquor recovered in Example 1 and pure water, control the mass fraction of phosphoric acid to 30%, add high-purity iron powder at a phosphorus-iron molar ratio of 2.5, place in a constant temperature water bath at 70℃, and stir at 300 rpm until the iron powder is completely dissolved; filter to remove undissolved residues to obtain a clear iron dissolution solution.

[0030] (2) Preparation of the base solution: Add pure water to the clear molten iron solution to dilute it, adjust the total iron mass concentration to 3.5%, and adjust the pH value of the system to 2.0; calculate the amount of titanium sulfate solution required to produce 8000ppm titanium phosphate based on the mass of anhydrous iron phosphate that can be obtained from the molten iron solution, dilute it with water by 6 times by mass, add all the diluted titanium solution to the above ferrous solution, stir and mix well to obtain the reaction base solution.

[0031] (3) First stage low temperature oxidation: Heat the reaction base liquid to 75℃, fix the stirring speed at 400rpm, and add the first stage hydrogen peroxide dropwise at a rate of 14mL / min. The amount of the first stage is 40% of the total hydrogen peroxide; the total molar amount of hydrogen peroxide is 1.4 times the total iron in the system.

[0032] (4) Second stage of high temperature oxidation and aging: After the first stage of addition is completed, the system is heated to 90°C. The remaining hydrogen peroxide is added at a rate of 14 mL / min while maintaining the same stirring speed. After the addition is completed, stirring is continued. Timing is started when the slurry turns completely pinkish-white. The slurry is kept at 90°C for 2 hours for aging.

[0033] (5) Filtration and washing: The aged slurry is filtered and the filter cake and aged mother liquor are collected separately; the filter cake is washed twice with pure water at 60℃, and the amount of water added each time is 4 times the mass of the filter cake.

[0034] (6) Drying and calcination: After washing, the filter cake is dried at 80℃ for 12h, crushed and calcined at 650℃ for 3h in air atmosphere, and then cooled and crushed to obtain titanium-doped iron phosphate product.

[0035] The finished product was found to contain 8116 ppm of titanium, and its various performance indicators are shown in Table 1.

[0036] Example 3 The steps and process parameters in Example 3 are basically the same as those in Example 1, except that the amount of titanium oxysulfate added to the base solution is adjusted: the amount of titanium oxysulfate solution required to produce 12,000 ppm titanium content is calculated based on the mass of anhydrous ferric phosphate that can be obtained from the molten iron solution. The other process parameters remain unchanged.

[0037] The finished product was found to contain 12,169 ppm of titanium, and its various performance indicators are shown in Table 1.

[0038] Example 4 The steps and process parameters in Example 4 are basically the same as those in Example 1, except that the amount of titanium oxysulfate added to the base solution is adjusted: the amount of titanium oxysulfate solution required to produce anhydrous iron phosphate with a titanium content of 16,000 ppm is calculated based on the mass of anhydrous iron phosphate that can be obtained from the molten iron solution. The other process parameters remain unchanged.

[0039] The finished product was found to contain 16094 ppm of titanium, and its various performance indicators are shown in Table 1.

[0040] Comparative Example 1 (One-step oxidation) The only difference between this comparative example and Example 1 is the oxidation method: hydrogen peroxide is added to the reaction base solution all at once without being added dropwise, and the reaction temperature is kept constant at 75°C. All other process parameters are exactly the same as in Example 1 (including the total molar amount of hydrogen peroxide, stirring speed, aging temperature and time, washing, drying, calcination conditions, etc.).

[0041] Testing revealed that the finished product contained 2876 ppm of titanium (target 4000 ppm). XRD patterns showed characteristic diffraction peaks of anatase TiO2, indicating that some titanium failed to incorporate into the crystal lattice and existed as free TiO2. SEM observation revealed aggregates of fine TiO2 particles on the particle surface. EDS surface scanning showed localized enrichment of titanium on the particle surface, with the internal titanium content significantly lower than the surface. The batch-to-batch titanium content fluctuated by ±580 ppm, far exceeding the ±200 ppm of Example 1.

[0042] Comparative Example 2 (Oxidation temperature in the first stage was too low) The only difference between this comparative example and Example 1 is the first oxidation temperature: the temperature of the first oxidation reaction is set to 40°C, and the other process parameters are exactly the same as those in Example 1.

[0043] Under these low temperature conditions, Fe 2+ The oxidation reaction kinetics were significantly slowed down, and the Fe in the system 2+ The phosphate was not fully oxidized (oxidation conversion rate was only about 60%), requiring the subsequent holding time to be extended to more than 2.5 hours to reach the target oxidation degree. The total oxidation time (dropping + holding) was much longer than in Example 1. The prolonged low reaction rate resulted in extremely slow and uneven nucleation of ferric phosphate, a small number of crystal nuclei, and ultimately abnormally large particles. The final product had a D50 of 18.6 μm, a wide and irregular particle size distribution, and a specific surface area reduced to 3.82 m². 2 / g. The titanium content is 3820ppm. EDS surface scanning shows that titanium is sporadically distributed within the particles, indicating significant segregation.

[0044] Comparative Example 3 (Oxidation temperature in the second stage was too high) The only difference between this comparative example and Example 1 is the second oxidation temperature: the temperature of the second oxidation reaction is set to 110°C, and the other process parameters are exactly the same as those in Example 1.

[0045] At a high temperature of 110℃, Fe 2+ The oxidation rate is extremely rapid; even before the hydrogen peroxide addition is complete, intense exothermic oxidation has already occurred in some parts of the system, leading to the oxidation of Ti. 4+ The hydrolysis rate increases dramatically, preferentially over Fe. 3+ Metatitanic acid was precipitated. XRD patterns showed TiO2 impurity phase diffraction peaks. EDS surface scanning revealed localized enrichment of titanium on the particle surface, with the internal titanium content being only about 60% of the surface content, indicating poor doping uniformity. The measured titanium content of the finished product was 3520 ppm, lower than the target value of 4000 ppm, indicating that some titanium existed as a free impurity phase and did not enter the crystal lattice.

[0046] Comparative Example 4 (Hydrogen peroxide droplet acceleration rate is too fast) The only difference between this comparative example and Example 1 is the hydrogen peroxide droplet acceleration rate: the hydrogen peroxide droplet acceleration rate for both the first and second stages is set to 35 mL / min, which is higher than the upper limit of 28 mL / min specified in this application. The other process parameters are exactly the same as those in Example 1.

[0047] Adding hydrogen peroxide too quickly can cause Fe 2+ The oxidation rate increases dramatically, and a large number of crystal nuclei form and grow rapidly in an instant. 4+ Before it could be evenly dispersed, it was encapsulated by precipitates. EDS line scan results showed that the titanium element in the particles exhibited a periodic, fluctuating distribution, rather than a uniform distribution. The finished product had a titanium content of 3860 ppm, with a D50 reduced to 3.12 μm. The particle size was too fine and the distribution was wide (span > 2.0), which was detrimental to the uniformity of mixing in the subsequent lithium iron phosphate preparation process. The titanium content within a single batch fluctuated by ±430 ppm, and the consistency was significantly worse than in Example 1.

[0048] Comparative Example 5 (Imbalance in hydrogen peroxide distribution ratio) The only difference between this comparative example and Example 1 is the hydrogen peroxide distribution ratio: the first part of hydrogen peroxide uses 90% of the total amount, and the second part of hydrogen peroxide uses 10% of the total amount. The remaining process parameters are exactly the same as in Example 1.

[0049] The first stage involved adding excessive hydrogen peroxide, resulting in a large amount of Fe. 2+ In the low-temperature stage, it is rapidly oxidized, with a large amount of iron phosphate forming nuclei, and the titanium source is co-precipitated before sufficient pre-dispersion; in the second stage, the oxidant is insufficient, and the remaining Fe... 2+ Oxidation was insufficient, and the reaction was incomplete. The finished product had a titanium content of 3640 ppm and an iron-to-phosphorus ratio of 0.930 (low, indicating an incomplete reaction). Some iron phosphate existed in an amorphous form, resulting in poor crystallinity. The XRD pattern showed no TiO2 impurity phase, but the FePO4 diffraction peak intensity was significantly weaker than in Example 1.

[0050] Comparative Example 6 (Irreduced titanium source added directly) The only difference between this comparative example and Example 1 is the method of adding the titanium source: the titanium oxysulfate stock solution is not diluted with water but directly added to the diluent. All other process parameters are exactly the same as in Example 1.

[0051] Upon addition of the undiluted titanium oxysulfate solution to the reaction substrate, the high local concentration of titanium ions led to rapid hydrolysis, generating metatitanic acid colloidal particles that could not be completely dispersed despite stirring. The filtered cake was a pale yellow, unevenly distributed color, with some areas showing white particles (metatitanic acid). The finished product contained only 2150 ppm of titanium, far below the target value of 4000 ppm, indicating a significant loss of titanium during washing and filtration. SEM observation revealed fine, irregular particles adhering to the particle surface, and EDS surface scanning confirmed that this adhering substance was a titanium-rich phase.

[0052] Table 1. Performance indicators of ferric phosphate in Examples 1-4

[0053] From the combined examples 1-4 and comparative examples 1-6, it can be seen that: This invention utilizes a synergistic process of "pre-dispersion of titanium + two-stage controlled oxidation" in a pure iron system to achieve linearly adjustable titanium content (deviation between measured and target values ​​≤5%) within a wide range of 4000–16000 ppm without the need for any external alkaline regulators. Furthermore, the product contains no free TiO2 impurities, titanium is uniformly distributed in the crystal lattice, and the titanium content fluctuation in a single batch is ≤±200 ppm. The product exhibits high purity (sulfur content ≤31 ppm, Na ≤16 ppm), concentrated particle size distribution (D50 = 6.51~6.76 μm), and good batch consistency.

[0054] When any key parameter deviates from the range defined in this invention, whether it is one-step oxidation (Comparative Example 1), oxidation temperature that is too low or too high (Comparative Examples 2 and 3), hydrogen peroxide droplet acceleration rate that is too fast (Comparative Example 4), hydrogen peroxide distribution ratio imbalance (Comparative Example 5), or titanium source that is not diluted and pre-dispersed (Comparative Example 6), it will lead to one or more problems such as titanium doping amount being significantly lower than the target value, free TiO2 or metatitanic acid impurity phase appearing, titanium element being enriched on the particle surface or exhibiting periodic fluctuation distribution, abnormally large or too fine particle size, and decreased crystallinity.

[0055] The above results show that the process parameter range defined by the present invention has strict criticality, and there is a synergistic relationship between each step. The parameter range cannot be easily obtained by those skilled in the art through conventional experiments. Instead, it overcomes the technical bias that titanium sources are easily hydrolyzed and difficult to simultaneously dope in the crystal lattice. It has outstanding substantive features and significant progress.

[0056] The above descriptions are merely embodiments of the present invention, and common knowledge regarding specific structures and characteristics is not elaborated upon here. It should be noted that those skilled in the art can make various modifications and improvements without departing from the structure of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.

Claims

1. A method for preparing titanium-doped iron phosphate using an iron-based method with adjustable titanium doping amount, characterized in that: Includes the following steps: S1. Iron dissolving reaction: Iron source is mixed with phosphoric acid to carry out an iron dissolving reaction, and the iron solution is obtained after filtration to remove impurities; wherein, the iron source is iron block or iron powder; S2. Dilution: Dilute the molten iron solution with water to adjust the total iron concentration and pH of the system, and obtain a diluted solution; S3. Preparation of the base solution: Calculate the required amount of titanium source to be added according to the target titanium doping amount, and then add the titanium source to the diluent and mix evenly to obtain the reaction base solution; S4. Preparation of hydrogen peroxide: Divide the hydrogen peroxide into two parts. The first part is 20% to 80% of the total amount of hydrogen peroxide used, and the second part is the remainder. S5. First stage low-temperature oxidation: The first part of hydrogen peroxide is added to the reaction substrate at a dropping rate of 2.8~28 mL / min to carry out the first oxidation reaction and obtain the first oxidation solution; wherein, the temperature of the first oxidation reaction is 55~85℃; S6. Second stage high-temperature oxidation: The second part of hydrogen peroxide is added to the first oxidation solution at a dropping rate of 2.8~28 mL / min to carry out a second oxidation reaction to obtain a second oxidation solution; wherein, the temperature of the second oxidation reaction is 80~100℃; S7. Aging: After the second oxidation solution turns pinkish-white, it is kept at a constant temperature for aging to obtain an aged solution; S8. Post-processing: The aging liquid is subjected to solid-liquid separation to obtain a filter cake. The filter cake is washed with pure water, dried, crushed, and calcined to obtain anhydrous titanium-doped iron phosphate product.

2. The method for preparing titanium-doped iron phosphate with adjustable titanium doping according to claim 1, characterized in that: In S1, the mass concentration of phosphoric acid is 15%~60%; the iron dissolution reaction is carried out under constant temperature water bath conditions, the water bath temperature is 25~90℃, stirring is required during iron dissolution, and the stirring speed is 150~500rpm; the phosphorus-iron molar ratio of phosphoric acid to iron source is 2.0~3.0; the purity of the iron block is ≥99.9%.

3. The method for preparing titanium-doped iron phosphate with adjustable titanium doping according to claim 1, characterized in that: In S2, the total iron mass concentration of the system is 2.5%~4.5%, and the pH is 1.8~2.

2.

4. The method for preparing titanium-doped iron phosphate with adjustable titanium doping according to claim 1, characterized in that: In S3, the titanium source is obtained by diluting a titanium oxysulfate solution with water; wherein the total mass of the diluted solution is 4 to 12 times the mass of the titanium oxysulfate solution before dilution.

5. The method for preparing titanium-doped iron phosphate with adjustable titanium doping according to claim 1, characterized in that: In S4, the total molar amount of hydrogen peroxide is 1.1 to 1.8 times the total molar amount of iron in the reaction substrate.

6. The method for preparing titanium-doped iron phosphate with adjustable titanium doping according to claim 1, characterized in that: In S5 and S6, both the first oxidation reaction and the second oxidation reaction require stirring, with a stirring speed of 200~600 rpm.

7. The method for preparing titanium-doped iron phosphate with adjustable titanium doping according to claim 1, characterized in that: In S7, the heat preservation and aging time is 1~4 hours.

8. The method for preparing titanium-doped iron phosphate with adjustable titanium doping according to claim 1, characterized in that: In step S8, the washing with pure water is performed at least twice, and the amount of pure water used in each wash is 4 to 6 times the mass of the filter cake to be washed. The washing temperature is 55 to 65°C. The aged mother liquor obtained after solid-liquid separation can be reused in step S1 to participate in the iron dissolution reaction. The drying temperature is 80 to 150°C, and the drying time is 3 to 12 hours. The calcination temperature is 600 to 700°C, and the calcination time is 2 to 6 hours.

9. A titanium-doped iron phosphate, characterized in that: The titanium-doped iron phosphate is prepared by any one of the preparation methods described in claims 1-8, wherein the titanium doping amount is 4000~16000ppm, the D50 is 6.51~6.76μm, and the specific surface area is 5-6m². 2 / g.

Citation Information

Patent Citations

  • A wet method for preparing titanium-doped iron phosphate

    CN111908441B